Charged-particle heating by electrostatic drift wave in the presence of an oscillating magnetic field - Misra K.D.; Tiwari M.S.; Gwal A.K. (My University, 2025)
The heating of charged particles in the presence of an oscillating magnetic field, directed perpendicular to the ambient magnetic field, is considered. The dispersion relation and the growth/damping rate for the electrostatic drift wave propagating perpendicular to the magnetic field are derived. The expressions for the change in energy of the plasma particles in parallel and perpendicular directions have been evaluated. It is found that the change in energy of the plasma particles in the parallel direction is much higher than in the perpendicular one. Applications of these results are discussed for the heating of laboratory and space plasma. © 1981 Società Italiana di Fisica.